The Effects of Total Quality Management Practices on Corporate Social Responsibility using Supply Chain Model: A Review of Malaysian Hotel Industry - Nazar, Nida; Jahan, Sarwat; Amoozegar, Azadeh; Anjum, Temoor; Raju, Valliappan (International Journal of Supply Chain Management, 2019)
The purpose of this paper is to investigate the impact of total quality management practices on corporate social responsibility in Malaysian hotels using supply chain management model, namely, supply chain operations reference model (SCOR). While considering the Malaysian hospitality industry, the database was developed. For a sample of 250 Malaysian hotels, with 3-5 stars, the database comprised of representative parameters related to CSR and TQM. These samples were considered a statistical population. During the last quarter of 2019, the fieldwork was conducted. The catalog, together with these parameters of examples of the hotel, was attained from surveys planned for the managers of the hotel by the researcher of the project. The final sample comprised of 81 % response rate from 202 hotels. This result was achieved after dropping the questionnaires (CSR and TQM) that were answered. It is observed that CSR hotel practices are positively influenced by high level of TQM practice with all independent variables i.e. I A (? = 0.42, t-value  = 5.15 , p-value 0.001), PM (? = 0.34 , t-value  = 3.21, p-value 0.01), SP (? = 0.29 , t-value  = 3.63 , p-value 0.01), CF (? = 0.39 , t-value  = 4.36 , p-value 0.001) and HRM (? = 0.45 , t-value  = 3.19 , p-value 0.001)   as predicted by H1 , H2 , H3 , H4 and H5 . Therefore, the data strongly supports the entire hypothesis. The structure of this paper is: firstly, the theoretical framework will be presented. Then the hypothesis related to the CSR and TQM effect will be introduced. After that, the empirical study, its methodology, and its findings will be explained. Lastly, the discussions on the results and conclusions are discussed.